High-scoring ielts writing model answers (based on past papers) - Fang Ting-Wang De Fu (Tổng hợp, 2014)
High-scoring IELTS Writing Model Answers (Based On Past Papers) High-scoring IELTS Writing Model Answers has the follow-ing important features:1. Selected IELTS actual tests2. Model essays from experienced teachers3. Strategy transfer4